Is one-stage lateral sinus lift and implantation safe in severely atrophic maxillae? Results of a comparative pilot study - Sascha Virnik; Laura Cueni; Anita Kloss-Brandstätter (SpringerOpen, 2023)
Abstract Purpose The aim of this retrospective comparative study was to evaluate the survival of dental implants placed in the posterior maxilla with a residual bone height less than 3 mm using a one-stage lateral sinus lifting approach. The research question was whether in very severely atrophied maxillary bones (residual height < 3 mm), a sinus lift with simultaneous implant placement would be associated with a higher complication rate compared to single-stage sinus lifts at average residual alveolar process heights. Methods Complications of 63 implants, where the residual bone height was below 3 mm, were compared to a reference group of 40 implants, which were inserted using a one-stage lateral sinus lift in maxillae with at least 3 mm residual bone height. Implant survival, bleeding-on-probing, the presence of peri-implant mucositis and the occurrence of peri-implantitis were documented. Results The mean follow-up time for implant survival was 80.3 ± 25.9 months. One implant out of 63 was lost in the severely atrophic maxilla group and two implants out of 40 were lost in the reference group. There were no differences in the occurrence of implant loss (p = 0.558), bleeding-on-probing (p = 0.087), peri-implantitis (p = 0.999) and peri-implant mucositis (p = 0.797) between the severely atrophic alveolar ridge group and the reference group. Conclusions Even in severely atrophic maxillae with < 3 mm residual bone height, a one-stage maxillary sinus lift and immediate implant placement can be carried out safely. Graphical Abstract